Acute upper gastrointestinal bleeding in liver cirrhosis patients - Svoboda, Pavel; Konecny, Michal; Martinek, Arnost; Hrabovsky, Vladimir; Prochazka, Vlastimil; Ehrmann, Jiri (Biomedical papers, 2012)
Objectives: . This study focuses on the etiology of acute upper gastrointestinal (GIT) bleeding in liver cirrhosis patients.Methods: A prospective examination of 137 liver cirrhosis patients with acute upper GIT bleeding. All patients underwent endoscopic examination and in the case of multiple findings, definition of the source of bleeding was based on the endoscopic report.Results: The most frequent causes of acute bleeding were: oesophageal varices (57.7%), peptic gastric and duodenal ulcers (18.2%), portal hypertension gastropathy (9.5%), gastric varices (5.1%), reflux oesophagitis (2.9%), Mallory-Weiss syndrome (2.9%) and erosive gastropathy (1.5%). A negative diagnosis was made in not more than 2.2% of patients. The majority of cases showed multiple findings in the upper digestive tract, each of which was a potential cause of bleeding. The mortality in all bleeding cirrhotic patients was 14.6%, 18.6% of which occurred in the varicose type of bleeding and 7.8% in the non-varicose type.Conclusions: Portal hypertension led to bleeding caused by varices and portal hypertension gastropathy in 72.3% of patients, 62.8% of patients suffered from purely varicose bleeding and 37.2% from non-varicose bleeding. Early, detailed endoscopic examination leading to appropriate diagnosis and treatment is of paramount importance.
Keywords: liver cirrhosis; portal hypertension; acute bleeding; peptic ulcer; endoscopy